MENEROKA ISU KAHWIN MUDA DALAM KALANGAN REMAJA PEREMPUAN DI KAMPUNG BELADIN, SARAWAK = (Exploring The Issue of Early Marriage among Teenage Girls in Kampung Beladin, Sarawak) - Nur Syaza, Massia; N. K., Tharshini (Universiti Sultan Zainal Abidin, 2023)
The issue of early marriage appears to be a trend among young adults. Therefore, this research was conducted to explore the problem more closely, specifically among teenage girls from rural areas. An in-depth interview was used to gather data on the factors and effects faced by teenage girls as a result of early marriage. The result shows that most of the informants involved in this study were between 17 and 21 years old, housewives, completed their studies until the Malaysian Certificate of Education, and married when they were 15. The findings disclosed four main contributing factors to early marriage: personal choice, out-of-wedlock pregnancy, financial deprivation, and parent’s insistence. Furthermore, the effects of early marriage include financial problems, negative perceptions from neighbors, and health struggles, especially during pregnancy. The output of this research is expected to have implications for stakeholders, who should re-evaluate marriage bills to protect the fundamental rights of teenage girls and prevent them from being persecuted for marrying young.